Improvements to a five-phase ABS algorithm for experimental validation - Gerard, Mathieu; Pasillas-Lépine, William; de Vries, Edwin; Verhaegen, Michel (Vehicle system dynamics, 2012)
The anti-lock braking system (ABS) is the most important active safety system for passenger cars. Unfortunately, the literature is not really precise about its description, stability and performance. This research improves a five-phase hybrid ABS control algorithm based on wheel deceleration [W. Pasillas-Lépine, Hybrid modeling and limit cycle analysis for a class of five-phase anti-lock brake algorithms, Veh. Syst. Dyn. 44 (2006), pp. 173-188] and validates it on a tyre-in-the-loop laboratory facility. Five relevant effects are modelled so that the simulation matches the reality: oscillations in measurements, wheel acceleration reconstruction, brake pressure dynamics, brake efficiency changes and tyre relaxation. The time delays in measurement and actuation have been identified as the main difficulty for the initial algorithm to work in practice. Three methods are proposed in order to deal with these delays. It is verified that the ABS limit cycles encircle the optimal braking point, without assuming any tyre parameter being a priori known. The ABS algorithm is compared with the commercial algorithm developed by Bosch.